Writing with Local Flavors: Developing Gastronomy-Based P5 Teaching Materials for Junior High Schools - Maisaroh, Siti; Darihastining, Susi; Wahyuniarti, Fitri Resti; Sari, Endah; Ulfa, Maria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Education plays a crucial role in shaping individuals who are not only academically competent but also possess strong character and cultural awareness. Within the framework of the Merdeka Curriculum, the implementation of the Pancasila Student Profile Strengthening Project (P5) serves as a strategic platform to instill these values through project-based learning. This study aims to develop teaching materials for writing procedural texts based on local gastronomy as a realization of the local wisdom theme in P5 at the junior high school level. The main issue addressed is the lack of teaching materials that integrate writing skills with the preservation and reinforcement of local culture. The research method employs a Research and Development (R&D) model using the systematic ADDIE approach. The developed teaching materials include five core components: an introduction to local gastronomy, understanding the structure of procedural texts, direct culinary observations, experience-based writing activities, and cultural reflection embedded in students' writings. Expert validation revealed a material and media feasibility rate of 92%. Limited trials in Grade VIII showed significant improvements in students’ procedural writing skills and their appreciation of local culture. The novelty of this study lies in the integration of local gastronomic exploration as a contextual and character-based literacy learning approach. This research is expected to contribute to the development of adaptive teaching materials that meet contemporary educational needs while promoting cultural preservation through Indonesian language learning under the Merdeka curriculum.